THE EVIDENTIAL SYSTEM FOR THE NON-PHYSICAL OFFENSE OF SEXUAL HARASSMENT - Hakki, Abdillah; Sadjijono, Prof. Dr. (jfpublisher, 2024)
Non-physical sexual harassment is not only about catcalls or whistling, but also includes sexual comments, commenting on body shape, flirting with affectionate words of a sexual nature, and showing vital organs constantly. Victims of verbal harassment are often frightened to report due to the lack of response from the community and law enforcement, and the lack of legal certainty. Verbal harassment victims are usually women, but can also be men or gay people. This research aims to increase the awareness of students and the public about sexual harassment cases, so that it is expected that there will be protection and resolution for cases of non-physical sexual harassment. This research uses a normative legal research method, which discusses legal principles, comparative law, legal history, and laws related to the crime of sexual harassment. The results of the analysis indicate that non-physical sexual harassment is verbal abuse in the public that can be committed by men or women by flirting, complimenting, or making sexual gestures to attract the victim’s interest. Sexual harassment, both physical and non-physical (verbal), targets the sexual organs or sexuality of the victim and must be resolved so that there are no more victims. It is expected that with the Sexual Harassment Law, the process of resolving and proving cases of sexual violence can be facilitated.